Sistem Informasi Manajemen Barang Habis Pakai Berbasis Web Dengan Menggunakan Model RAD - Fauzan Aziz; Sujono Sujono (STMIK Banjarbaru, 2026)
Conventional management of consumable goods at RSUD Drs. H. Abu Hanifah, Koba, Central Bangka Regency requires an average of 47.2 minutes per procurement request cycle and frequently encounters data discrepancies due to the absence of real-time stock information. This study aims to develop a Web-based Consumable Goods Management Information System to address these issues. The system was built using the Rapid Application Development (RAD) model with a three-tier architecture (PHP/Laravel, MySQL, Bootstrap 5) across four phases completed within 11 weeks. Key innovations include a two-level digital authorization workflow and a real-time stock restriction mechanism enforced at the user level. The system was evaluated using Black Box Testing across 20 functional requirements and the System Usability Scale (SUS) involving 15 respondents. Results demonstrate a 100% functional pass rate, an 85.6% reduction in average processing time (from 47.2 to 6.8 minutes), and a mean SUS score of 81.3, classified as Good.Keywords: Information System; Inventory Management; Consumable Goods; Rapid Application Development; Efficiency. AbstrakPengelolaan Barang Habis Pakai (BHP) secara konvensional di RSUD Drs. H. Abu Hanifah, Koba, Kabupaten Bangka Tengah memerlukan rata-rata 47,2 menit per siklus permohonan dan sering mengalami ketidaksesuaian data akibat tidak adanya informasi stok secara real time. Penelitian ini bertujuan membangun Sistem Informasi Manajemen BHP berbasis web yang mampu mengatasi permasalahan tersebut. Sistem dikembangkan menggunakan model Rapid Application Development (RAD) dengan arsitektur three-tier (PHP/Laravel, MySQL, Bootstrap 5) melalui empat fase selama 11 minggu. Kebaruan sistem mencakup alur otorisasi digital dua tingkat dan mekanisme restriksi stok real time di sisi pengguna. Pengujian dilakukan dengan Black Box Testing untuk 20 kebutuhan fungsional dan System Usability Scale (SUS) terhadap 15 responden. Hasil menunjukkan tingkat kelulusan fungsional 100%, reduksi rata-rata waktu proses sebesar 85,6% (dari 47,2 menjadi 6,8 menit), dan skor SUS rata-rata 81,3 (kategori Good).